Delayed immune mediated adverse effects to hyaluronic acid fillers: report of five cases and review of the literature - Ora Bitterman-Deutsch; Leonid Kogan; Faris Nasser (PAGEPress Publications, 2015)
Hyaluronic acid (HA) fillers in cosmetic medicine have been considered relatively safe, though fillers used in European countries and throughout the world are not necessarily approved by the Food and Drug Administration. As their use continues to expand worldwide, physicians in a wide range of medical specialties are authorized to perform HA injections, including general medicine practitioners and even dentists. An increasing number of reports have appeared regarding side effects to these products. It is now known that reactions to Hyaluronic acid are related not only to technical faults of the injections, but also to immune responses, including delayed hypersensitivity and granulomatous reactions. Herein, we describe five cases treated by a variety of treatment modalities, all with delayed reactions to different brands of hyaluronic acid fillers. As there is currently no standardization of treatment options of adverse effects, these cases accentuate the debate regarding the approach to the individual patient and the possible need for pre-testing in patients with an atopic tendency.